A Study on Tourist Satisfaction of Fujian Traditional Village Tourism Based on Perceived Value - Zhang, Qianqian; Satchapappichit, Sruangporn; Zhao, Chuanhai (Migration Letters, 2023)
The traditional village is a carrier of profound ethnic history and cultural heritage. However, it is facing unprecedented dual challenges of "protective decay" and "constructive decay" in an open environment, posing severe challenges to inheritance and development in the process of modernization. In recent years, traditional villages rich in cultural heritage and scenic resources have exhibited strong appeal to tourists. Nonetheless, issues persist, such as low tourist satisfaction with tourism products, inadequate professionalism among service providers, and weak market competitiveness, which hinder these traditional villages from meeting market demands. In this context, exploring the relationship between tourist perceived value, satisfaction, and loyalty can enhance the competitive edge of traditional villages in Fujian’s tourism market. From the perspective of tourist perception, an evaluation model of "perceived value - satisfaction - loyalty" was constructed and empirically studied. The model consists of three major factors: tourist perceived value, tourist satisfaction, and tourist loyalty, along with 33 observed factors influencing these three main factors, forming a linear structural relationship. The results indicate that, in addition to societal value, various aspects of perceived value such as scenic value, cost value, emotional security value, service value, project facilities value, and convenient transportation value all significantly positively influence tourist satisfaction in Fujian’s traditional village tourism. Tourist satisfaction also significantly positively affects tourist loyalty, while tourist perceived value indirectly influences loyalty through satisfaction. The influencing paths of each variable are not identical. Based on this, focusing on the aspect of perceived value in traditional village tourism, recommendations are provided for the development of traditional village tourism in Fujian.